Ambivalent sexism predicts Israelis’ gendered preferences in the Gaza hostage crisis - Orly Bareket; Michal Reifen-Tagar; Tamar Saguy (Communications Psychology)
Abstract Gender-based prioritization in life-or-death decisions has long shaped crisis responses, from natural disasters to wartime evacuations. This study examined psychological predictors of public support for such prioritization, using the case of Israeli hostages abducted by Hamas terrorist organization on October 7, 2023. Across two hostage release deals—one in November 2023 and another in January 2025—women were systematically prioritized, leaving abducted men in captivity. Analyses of a representative Jewish Israeli sample (N = 1171) regarding the November 2023 deal, reveal that hostile sexism, marked by resentment toward women, predicts opposition to prioritizing women’s release. Conversely, benevolent sexism, casting women as needing protection, predicts support for women’s prioritization (particularly for mothers). Even after accounting for demographics and broader ideologies, sexist attitudes emerge as key predictors of gender-based preferences in public opinion. Hostile and benevolent sexism operate here largely independently, with no credible evidence for an interaction, suggesting distinct psychological pathways. Respondent’s gender plays a minor role, though benevolent sexism predicts a stronger protective bias toward women hostages among men than among women. These findings underscore how hostile sexism can disadvantage women, while benevolent sexism can reinforce women’s vulnerability but demands men’s sacrifice. Although decisions about hostage release may appear purely pragmatic on the surface, divergent public views on the matter may reflect gendered biases that emerge in high-stakes, life-or-death contexts—potentially more than impartial, need-based considerations.